Identifikasi Tingkat Stress Setelah Dilakukan Biblioterapi pada Anak yang Dilakukan Tindakan Invasif di Rumah Sakit - Reni Ilmiasih (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2019)
Children treated in hospitals have problems stressing the impact of hospital care, especially invasive actions. The efforts of pain management have been carried out mostly is the management of physical pain and the results of the research obtained are not fully optimal. Psychological children also need to be prepared besides physical management. Anxiety, fear and not understanding the procedure will contribute to the perception of pain. The purpose of this study was to identify stress levels in children who were infared after bibliotherapy. The research method chooses descriptive research with 15 quota sampling techniques. The data analysis used is descriptive analytic. Phase 1 of the Basic Scientific Research (PDK) research by performing psychological pain management using bibliotherapy, the storytelling method was obtained after bibliotherapy with a description of patients in the hospital as much as 2x a day and 50% of respondents experienced mild stress. This is because the bibliotherapy process with stories of children being treated in hospitals is able to make a picture of the situation that can be understood in preparing mentally for infasive actions. Keywords: Stress, Children, Bibliotherapy, invasive measures